A Systematic Review of Fun Cooking Activities for Strengthening Children's Measurement Skills in STEM Education - Dewi Rahmawati; Titi Chandrawati; Erie Siti Syarah (Murhum : Jurnal Pendidikan Anak Usia Dini, 2025)
Measurement skills are an important foundation in early childhood mathematics and science learning and play a role in building STEM readiness. Fun cooking activities, especially those based on traditional foods, provide concrete experiences that help children understand the concepts of weight, volume, and proportion in a cultural context that is close to their lives. This study is a systematic review using the PRISMA guidelines and the Scopus, Web of Science, ERIC, SpringerLink, and Google Scholar databases. Of the 327 studies identified, 28 articles met the inclusion criteria and were analyzed thematically. The results show that fun cooking can improve children's quantitative understanding, while the use of traditional foods reinforces the relevance of learning and cultural values. Teacher and parental guidance plays an important role in the scaffolding process, although challenges such as limited tools and curriculum adaptation are still found. Culture-based fun cooking is an effective approach to support measurement skills in early childhood STEM education, but further research is needed to assess the long-term impact.